1994
DOI: 10.1016/0014-5793(94)80501-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 23 kDa subunit of tau protein kinase II as a putative activator of cdk5 in bovine brain

Abstract: Tau protein kinase II (TPKII) was reported previously to be composed of a neuron-rich cdc2-related kinase (PSSALREfcdkS) and 23 kDa subunit. Here we show that the 23 kDa subunit is a putative activator for the kinase activity. Amino acid sequence analysis revealed that the protein was novel and included a partial similarity of amino acids to a cyclin box important for the interaction with cdc2-related kinase. These results suggest that the 23 kDa subunit, but not cyclin, activates cdk5 in neuronal cells, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 37 publications
2
93
0
Order By: Relevance
“…Cdk5 and p35 cloned from bovine retina have the same cDNA sequences as those of bovine brain proteins (20). We note that recombinant p35 is expressed as a ϳ25-kDa protein, as described previously (22)(23)(24). The ϳ25-kDa protein (p25) is a truncated form of p35, but p25 has been shown to activate Cdk5.…”
Section: Methodsmentioning
confidence: 99%
“…Cdk5 and p35 cloned from bovine retina have the same cDNA sequences as those of bovine brain proteins (20). We note that recombinant p35 is expressed as a ϳ25-kDa protein, as described previously (22)(23)(24). The ϳ25-kDa protein (p25) is a truncated form of p35, but p25 has been shown to activate Cdk5.…”
Section: Methodsmentioning
confidence: 99%
“…Full-length p35 contains 307 amino acids and the originally identified 25-kDa proteolytic fragment of p35 contains residues 99 -307. The 25-kDa proteolytic fragment is active in vivo (15,24) and in vitro when expressed in bacteria as a GST-fusion protein (26,32). A GST-fusion protein containing residues 109 -291 (designated as GST-p25 here) is also active as a Cdk5 activator (32).…”
Section: Identification Of Binding and Activating Domains Of The Cdk5mentioning
confidence: 99%
“…Cdk5 is able to phosphorylate tau on sites that are abnormally phosphorylated in Alzheimer's paired helical filaments (22,23). The 25-kDa subunit of the Cdk5 kinase (15,24) was later found to be a proteolytic fragment of a larger 35-kDa protein (p35) (14,25,26). An isoform of p35 that shares 57% amino acid identity to p35 has been identified, and its mRNA is predominantly expressed in the hippocampus (27).…”
mentioning
confidence: 99%
“…Like other members of the cyclin-dependent kinase family, cdk-5 activity requires association with a regulator, and recent studies have identified two homologous cdk-5 activators, p35 and p39flCksal (Ishiguro et al, 1994;Lew et al, 1994;Tsai et al, 1994;Tang et al, 1995). A further unrelated stimulator of cdk-5 activity, p67, which is identical to Munc-18, a component of synaptic vesicle fusion protein complexes, has also been described (Hata et al, 1993;Shetty et al, 1995).…”
mentioning
confidence: 99%